Evaluation of the Toxicity of Hemizygia bracteosa (Benth) Plant Used in Traditional Medicine for the Treatment of Diabetes Mellitus in Benin - CHABI, NICODÈME WOROU; KONFO, Christian Tétédé Rodrigue; ADJAGBA, Marius; MOUSSEDIKOU, Loukman; DAHOUENON EPOUSE AHOUSSI, EDWIGE; LALEYE, OLABISSI ANATOLE A.; GBAGUIDI, Christophe; SOUMANOU, MANSOUROU MOHAMED (My University, 2015)
Abstract This study aims to assess the toxicity of Hemizygia bracteosa (Benth), a medicinal plant used for the treatment of diabetes mellitus in Benin. Wistar rats were force-feeded by using solutions obtained by dissolving the powder of this plant in distilled water. The assessment of biochemical parameters (blood glucose, triglycerides, cholesterol, HDL cholesterol, proteins) of Wistar rat serum was used to highlight the hypoglycaemic properties of this plant and its effects on cardiovascular risk factors. The results showed an increase in HDL-cholesterol levels (0.13 ± 0.004 vs 0.48 ± 0.15) and a decrease in total cholesterol levels (1.06 ± 0.40 vs 0.81 ± 0.12), triglycerides (1.2 ± 0.43 vs 1.18 ± 0.38), glucose (1.60 ± 0.25 vs 0.98 ± 0.24) and proteins (95. 33 ± 20.59 vs 58.30 ± 6.26) in rats serum after one month treatment. No significant differences were observed in control rats for all parameters. our data also shows that at concentrations from 2 g/kg this plant appears topresent significant toxicity on kidneys and liver. The use of this plant for diabetes treatment must be done with caution and doses must be controlled.
Keywords: diabetes mellitus; traditional medicine; toxicity; Hemizygia bracteosa (Benth); Benin